(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article discusses the relevance and importance of rehabilitation after abdominal surgery. Modern methods of recovery, such as early activation, diet therapy, physiotherapy procedures and psychological support, were analyzed. The basis for the study was data from scientific sources and databases Google Scholar, Scopus and PubMed. The results of the analysis show that early and comprehensive rehabilitation reduces the risk of complications and accelerates the recovery process of patients. The findings highlight the need for further improvement of rehabilitation programs to improve the quality of life of patients in the postoperative period.